The Correlation between EFL Students' Anxiety and Their English Writing Skills - Wira Kafryawan; Andi Miftahul Maulidil Mursyid; Rahmawansyah Sahib; Heni Purwati (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2021)
Anxiety in writing contains tension, nervousness, worry, and a wide variety of other negative feelings when someone is given a task to write in a certain situation. The objective of this study is to figure out whether or not there is a significant correlation between EFL students' anxiety and their English writing skills. The subject of the study is the fourth semester of EFL students in the State Islamic Institute of Fattahul Muluk Papua. The study focused on a correlational method of two quantifiable variables involving anxiety and English writing skills. Two instruments are used in this study including Foreign Language Writing Anxiety Inventory (FLWAI) developed by Cheng and the writing test developed by Heaton. The samples are 40 EFL students as the respondents and the data were calculated by Pearson product-moment. The findings reveal that there is a significant correlation between EFL students’ anxiety and their English writing skills at a high level. It means that the lower anxiety belongs to EFL students, the better they write in English. Moreover, cognitive anxiety is the most influential anxiety on EFL students’ English writing skills. Then, it is followed by somatic anxiety, and avoidance behavior is also fairly influential.